Dzieje szkolnictwa gromady Mścice (1954–1972) na tle przemian oświatowych - Skonieczny, Tomasz (Biuletyn Historii Wychowania, 2011)
On the basis of the archival material, the article presents the process of formation and development of Polish schools in Mścice commune against the background of the post-war educational transformations in Poland (until 1972). The author focuses on the problems that accompanied the transformations, such as: the lack of the teaching personnel (especially qualified), numerous changes of offices, the insufficiency of funds, of equipment and housing as well as the subordination of schools to the communist ideology which dominated in Poland at that time. Furthermore, the article presents the reforms connected with the educational system between 1954–1972 and their impact upon the teaching personnel and the material base. The final caesura of the article coincides with the end of Mścice commune.